Practicing equity-centered improvement: a design tensions perspective - Resnick, Alison Fox; Farrell, Caitlin C.; Bristol, Jackquelin (Frontiers in Education, 2025)
Equity-centered improvement is—necessarily—deeply relational, political, and adaptive. Improvers must regularly navigate uncertainty, negotiate conflicting priorities, and make situated decisions amidst organizational, political, and interpersonal constraints. However, too often, research and guidance focus on naming what improvers should do, with less attention to how improvers actually engage in the ongoing, improvisational, judgment-filled work of practicing improvement for equity. This conceptual article introduces design tensions as a conceptual tool for naming and navigating ongoing tradeoffs that arise in equity-centered change efforts. Drawing on existing research, we describe three design tensions: (1) reconciling needs for timeliness, learning, and collaboration, (2) negotiating between clarity for action and systemic complexity, and (3) mediating political dynamics and systemic disruption. We propose that practicing equity-centered improvement involves ongoing satisficing within these tensions and examine the potential power of bringing the lens of these tensions into the practice of, learning about, and study of equity-centered improvement.